THE RECOGNITION OF CAVITARY RETINOBLASTOMA TUMORS: Implications for Management and Genetic Analysis. Issue 4 (April 2018) - Chaudhry, Shabana; Onadim, Zerrin; Sagoo, Mandeep S.; Reddy, M. Ashwin
Abstract : Purpose: To assess the role of consolidating adjuvant therapy for cavitary retinoblastoma and to understand if there is any phenotype–genotype correlation. Methods: Patients with retinoblastomas having ophthalmoscopically visible cavities between 2004 and 2014 in whom 4 to 6 cycles of systemic chemotherapy were given. Results: Eighteen eyes of 17 patients displayed cavitary retinoblastomas. This represented 6.8% of 250 patients. Mean age at diagnosis was 13 months; 5 unilateral (29%) and 12 bilateral (71%). The mean (median, range) number of retinoblastoma tumors per eye was 2 (2; 1–6). The number of cavities per tumor was 3 (2, 1–6). Intratumoral cavities were seen in the superficial portion of the tumor in 10 eyes (55%). The cavities became visible in eight eyes (44%) and collapsed in eight eyes (44%). Two eyes required enucleation because of relapse in noncavitary tumors. Germline mutations were detected in 14 patients (82%) of whom four demonstrated mosaicism (29%); only one had a low penetrant mutation. The mean follow-up period was 40 (35, 6–120) months. Conclusion: Cavitary retinoblastomas can be detected after systemic chemotherapy with cavities becoming visible after mean two cycles of chemotherapy (secondary cavitary retinoblastoma). The etiology is uncertain. They remain stable and do not require aggressive adjuvant therapy. There was no evident phenotype–genotype correlation with mosaicism noted in 29%. Abstract : Supplemental Digital Content is Available in the Text.Cavities in retinoblastoma tumors can be detected after systemic chemotherapy. The detection of cavities confers stability and aggressive consolidation therapy is not required.